Development of a training model for calculating traditional snack production costs with a comparative raw material approach to improve MSME business capabilities - Murwenie, Ira; Kartiko, Erik; Hassanudin, Abdul Fatah; Avrianto, Alam; Kurnaeli; Sujana, Duduh; Puspa, Rahmina (Jurnal Pembelajaran Pemberdayaan Masyarakat (JP2M), 2025)
This community service program developed a structured training model to enhance the business capabilities of Micro, Small, and Medium Enterprises (MSMEs) in the traditional snack sector, focusing on production cost calculation using a comparative raw material approach. Many MSMEs face challenges in optimizing costs and setting appropriate prices, which reduces profit margins. The training was designed to strengthen participants’ analytical skills in determining production costs, calculating selling prices, and projecting profits by comparing alternative raw materials. Evaluation of the program was conducted through pre-tests and post-tests to measure knowledge improvement regarding cost analysis and raw material management. Statistical analysis revealed a t-test value of 0.9306, indicating a significant improvement in participants’ understanding and practical ability to apply cost calculation methods after the training. These results demonstrate that the training model effectively enhances MSME actors’ capacity to optimize production processes, manage resources more efficiently, and make better-informed strategic decisions. Overall, the model shows strong potential to support MSME sustainability and competitiveness in the traditional snack industry.